Mastering of Technology of Production of Brucellosis Diagnostic Bacteriophages - L. V. Lyapustina; P. A. Omelyanchuk; G. I. Lyamkin; S. V. Vilinskaya; S. I. Golovneva; O. I. Kogotkova; D. A. Budyka; D. V. Rusanova; A. N. Kulichenko (Проблемы особо опасных инфекций, 2009)
Presented are technologies of production of brucellosis diagnostic bacteriophages developed on the basis of determination of optimal conditions of the phages reproduction. Stability of the finished product was evaluated using Shuhard control charts.